Injection Anxiety and Pain in Men Using Intracavernosal Injection Therapy after Radical Pelvic Surgery. (30th July 2013) - Nelson, Christian J.; Hsiao, Wayland; Balk, Eliana; Narus, Joseph; Tal, Raanan; Bennett, Nelson E.; Mulhall, John P.
Abstract Introduction Intracavernosal injection (ICI) therapy is a well‐recognized treatment strategy with high success rates for men with erectile dysfunction. Despite this, injection anxiety and pain related to injection are significant barriers to its use. Aims This study aims to examine injection anxiety and injection pain in patients using ICI. Methods Men starting ICI therapy post radical pelvic surgery completed questionnaires at initial visit, at each of the two ICI training sessions and at a 4‐month follow‐up visit. Main Outcome Measures Injection Anxiety Scale, Injection Pain Scale, Injection Reaction Inventory, and the Erectile Function Domain of the International Index of Erectile Function. Results Average age of the 68 men was 60 ± 8 years. At 4 months, the self‐reported frequency of ICI use was: 29% <1/week, 26% 1/week, 40% 2/week, and 5% 3/week. Mean injection anxiety score at first injection was 5.7 ± 2.8 (range 0–10) and significantly decreased to a 4.1 ± 3 at 4 months (P < 0.001). At first injection, 65% reported high injection anxiety (≥5) and this significantly decreased to 42% (P = 0.003) at 4 months. Anxiety at first injection was negatively related to ICI frequency at 4 months (r = −0.23, P = 0.08). Mean injection pain score at first injection was low (2.2 ± 1.8, range 0–10) and 59% rated injection pain ≤2. Injection pain remained consistent across time periods. At first injection, injection anxiety (assessed prior to injection) was related to injection pain (r = 0.21, P = 0.04) and subjects (n = 21) who reported high injection anxiety (≥5) across time points, reported an increase in injection pain scores from first injection to 4 months (2.7 vs. 3.7, P = 0.05). Conclusions Although injection anxiety decreased with ICI use, mean injection anxiety remained at a moderate level (4.4) and 42% of men continued to report "high" injection anxiety at 4 months. While injection pain was low, injection anxiety and pain were related. These data suggest the need for a psychological intervention to help lower injection anxiety related to ICI. Nelson CJ, Hsiao W, Balk E, Narus J, Tal R, Bennett NE, and Mulhall JP. Injection anxiety and pain in men using intracavernosal injection therapy after radical pelvic surgery. J Sex Med 2013;10:2559–2565.